Ethics and spirituality in the workplace: The growing role of the business case in reforms. Issue 5 (13th July 2015) - Freeman, Tim; Kunter, Aylin; Douglas, Carlis; Roper, Ian
Abstract : Purpose: – Draws attention to recent broad trends in UK employment regulation that refocus the emphasis in employment rights away from a primary concern with safeguarding collective rights toward a more differentiated approach privileging more individual concerns. Design/methodology/approach: – Seeks to explain the reasons and consequences of this development. Findings: – Argues that rights are defended on the basis of their ability to secure greater employee motivation and productivity. Practical implications: – Explains that this is a business-case defense rather than a requirement for social justice. Social implications: – Advances the view that modern Conservatives see society as made up of a broad range of actors and not reducible to state action. Originality/value: – Claims that the extension of the minimum period of employment required before an employer may be taken to tribunal to two years, together with a greatly increased fee required to bring a case, mean that cases are much more difficult to make.